Juego dramático y pensamiento (1995)
ABSTRACT: This paper calls attention to children's Theatrical Expression. Specifically an important aspect of this expression namely Dramatic Play. This activity not only allows educators to know students' psychological processes better, but also nurtures and encourages their creative development. A program in Theatrical Expression based on Dramatic Play is strongly related to this three áreas: 1) cognitive thinking development (i.e. space and time construction, events coherence and relationship, reality comprehension, problem solution, critical thinking); 2) affective development (self-esteem processes, social interaction, confidence in supporting the own ideas and listening others), and 3) creative development (fluency, flexibility, originality and elaboration). Although Drama! The Play has been recognized and widely used during the pre-school years, it is extremely ignored after a child enters the first grade. To improve our understanding about this important activity, this paper invites to study its dynamics and evolution in late childhood, and ils relationship with other areas of children's psychological development. In this way, teachers can enrich their daily classroom interaction, and encourage programs of Theatrical Expression that complement the Art curriculum.